2005
DOI: 10.1158/0008-5472.can-05-0370
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid Targeting of Different D-Type Cyclins through Distinct Chemopreventive Mechanisms

Abstract: D-type cyclins (cyclins D1, D2, and D3) promote G 1 -S progression and are aberrantly expressed in cancer. We reported previously that all-trans-retinoic acid chemoprevented carcinogenic transformation of human bronchial epithelial (HBE) cells through proteasomal degradation of cyclin D1. Retinoic acid is shown here to activate distinct mechanisms to regulate different D-type cyclins in HBE cells. Retinoic acid increased cyclin D2, decreased cyclin D3 and had no effect on cyclin D1 mRNA expression. Retinoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
3
28
1
Order By: Relevance
“…This indicates that ubiquitin-targeted proteasomal degradation of cyclin D1, Id2 or any other proliferation-promoting factor is unlikely to play a major role in mechanisms of the antiproliferative action of retinoids in human keratinocytes. It should be noted, however, that besides the use of different cell lines, retinoic acid concentrations used in experiments reported by Ma et al (2005) were about two orders of magnitude higher than those used in our study. It is conceivable that higher doses are required to activate the proteasomal regulatory pathway.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…This indicates that ubiquitin-targeted proteasomal degradation of cyclin D1, Id2 or any other proliferation-promoting factor is unlikely to play a major role in mechanisms of the antiproliferative action of retinoids in human keratinocytes. It should be noted, however, that besides the use of different cell lines, retinoic acid concentrations used in experiments reported by Ma et al (2005) were about two orders of magnitude higher than those used in our study. It is conceivable that higher doses are required to activate the proteasomal regulatory pathway.…”
Section: Resultscontrasting
confidence: 63%
“…It has been reported that retinoic acid does not affect levels of cyclin D1 mRNA, but promotes the ubiquitination and consequent degradation of cyclin D1 protein, and that proteasomal inhibitors block retinoid-induced decline in cyclin D1 (Ma et al, 2005). In a different experimental system, glucocorticoid-induced decline in proliferation of neural stem cells was abrogated in the presence of 0.5 mM of a potent proteasomal inhibitor MG132, reflecting an involvement of the ubiquitin proteasomal pathway (Sundberg et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
“…BEAS-2B immortalized HBE cells were cultured in serum-free LHC-9 medium (Biofluids, Rockville, MD) as described (32). Nontumorigenic murine C10 alveolar type II epithelial cells (33) were cultured in CMRL 1066 medium (Life Technologies, Grand Island, NY) supplemented with 10% FBS, 2 mM L-glutamine, 100 units/ml penicillin, and 100 g/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The GL2 siRNA (Dharmacon, Lafayette, CO) served as a control. Transfection was performed as described (32). Viable BEAS-2B cells were measured by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (34).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, DNA damage causes specific degradation of cyclin D1, but not cyclin D2 or D3 (Agami and Bernards, 2000). Moreover, although retinoic acid upregulates the expression of cyclin D2, it downregulates expression of cyclin D1 in a manner dependent on Thr286 and GSK3b or that of D3 in a manner independent of Thr283 and GSK3b (Ma et al, 2005). In this regard, it is also notable that the role of GSK3b in phosphorylation of cyclin D1 or D3 has recently been challenged (Casanovas et al, 2004;Okabe et al, 2006;Yang et al, 2006).…”
mentioning
confidence: 99%